2015
DOI: 10.1103/physrevb.91.174506
|View full text |Cite
|
Sign up to set email alerts
|

Pressure studies of the quantum critical alloyCe0.93Yb0.07CoIn5

Abstract: Here we present our experimental and theoretical study of the effects of pressure on the transport properties of the heavy-fermion alloy Ce1−xYbxCoIn5 with actual concentration x ≈ 0.07. We specifically choose this value of ytterbium concentration because the magnetic-field-induced quantum critical point, which separates the antiferromagnetic and paramagnetic states at zero temperature, approaches zero, as has been established in previous studies. Our measurements show that pressure further suppresses quantum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 53 publications
3
40
1
Order By: Relevance
“…[19]. Combining this result with our present RNCCSD calculations, d a = 0.49 × 10 −20 σ C T ecm and d a = 0.32 × 10 −17 S/(|e| fm 3 ) |e|cm, and assuming that the EDM is due to a single source of either the NSM or the T-PT interaction, we obtain, respectively, the following upper limits |S| < 4.7 × 10 −10 |e|fm 3 (25) and…”
supporting
confidence: 66%
See 2 more Smart Citations
“…[19]. Combining this result with our present RNCCSD calculations, d a = 0.49 × 10 −20 σ C T ecm and d a = 0.32 × 10 −17 S/(|e| fm 3 ) |e|cm, and assuming that the EDM is due to a single source of either the NSM or the T-PT interaction, we obtain, respectively, the following upper limits |S| < 4.7 × 10 −10 |e|fm 3 (25) and…”
supporting
confidence: 66%
“…The theoretical foundations of Xe EDM were laid in a series of seminal papers by Flambaum and co-workers [21][22][23][24]. There have been recent advances in the relativistic manybody calculations of the EDM of this atom [8,25]. The results of these calculations are necessary for extracting CP violating coupling constants from the measured values of Xe EDM [8,25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the anomalous physical properties exhibited by Ce 1−x Yb x CoIn 5 [172,173,174], numerous studies have been performed to probe this system's superconducting and normal state properties [179,180,181,182,183]. Interestingly, near x = 0.2 (x act 0.067), an intriguing crossover is observed.…”
Section: Magnetism Quantum Criticality and Superconductivitymentioning
confidence: 93%
“…Furthermore, from careful measurement of the in-plane magnetoresistivity of Ce 1−x Yb x CoIn 5 in magnetic fields up to 14 T [180], it has been shown that the quantum critical field associated with the fieldinduced quantum critical point (H QCP = 5 T for CeCoIn 5 ) is suppressed to 0 T near x = 0.2; therefore, the quantum critical point is suppressed by Yb substitution and the non-Fermi liquid behavior that persists to much higher Yb concentrations in Ce 1−x Yb x CoIn 5 must be decoupled from its associated quantum criticality [180]. It has also been shown that quantum critical fluctuations near x = 0.2 are suppressed with increasing pressure [183]. Despite all of these dramatic transitions and crossovers near x = 0.2, there is no apparent feature in T c (x) at this concentration.…”
Section: Magnetism Quantum Criticality and Superconductivitymentioning
confidence: 93%